2019
DOI: 10.3389/fpls.2019.00662
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of 2 Phosphate Starvation-Inducible Phosphocholine/Phosphoethanolamine Phosphatases, PECP1 and PS2, in Arabidopsis

Abstract: Phosphorus is essential for plant viability. Phosphate-starved plants trigger membrane lipid remodeling to replace membrane phospholipids by non-phosphorus galactolipids presumably to acquire scarce phosphate source. Phosphoethanolamine/phosphocholine phosphatase 1 (PECP1) and phosphate starvation-induced gene 2 (PS2) belong to an emerging class of phosphatase induced by phosphate starvation and dephosphorylates phosphocholine and phosphoethanolamine (PEtn) in vivo . However, detailed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…For P. ginseng growth, the P-starved root might require some metabolism of P-containing proteins to cope with the P starvation. Under a P-starved condition, a slight but significant reduction of phosphoethanolamine was detected in Arabidopsis roots; this result indicates that phosphoethanolamine can be dephosphorylated in the phospholipids under P starvation 40,41 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…For P. ginseng growth, the P-starved root might require some metabolism of P-containing proteins to cope with the P starvation. Under a P-starved condition, a slight but significant reduction of phosphoethanolamine was detected in Arabidopsis roots; this result indicates that phosphoethanolamine can be dephosphorylated in the phospholipids under P starvation 40,41 .…”
Section: Resultsmentioning
confidence: 85%
“…The P. ginseng sprouts might respond to the P deficiency in our study even though N and K were readily available for rapid growth. Under the P-starved condition, metabolic conversion of phosphoethanolamine to 2-aminoethanol occurs in the phospholipids to cope with the P starvation 40 , 41 . Following the decrease of phosphoethanolamine, methionine might be required less in P. ginseng sprouts as a methyl group donor for phosphoethanolamine.…”
Section: Resultsmentioning
confidence: 99%
“…AtPECP1 displayed significant specific activity for PEA and PCho in vitro (May et al, 2012). A subsequent study showed that both AtPECP1 and AtPECP2 are involved in PEA and PCho metabolism in vivo (Angkawijaya et al, 2019; Angkawijaya & Nakamura, 2017; Hanchi et al, 2018). Although the recombinant OsACP1 protein shows the highest activity for PEA as AtPECP1 does, OsACP1 can also effectively hydrolase several other kinds of Po (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…OsHAD1 , which is renamed as OsHAD12 by phylogenetic analysis, is proposed to regulate Pi acquisition by dephosphorylation of downstream target proteins in the cytosol (Pandey et al, 2017). AtPECP1 and AtPECP2 (also name as AtPS2/AtPPsPase1), are reported to hydrolyse phosphocholine (PCho) and phosphoethanolamine (PEA) under Pi starvation conditions in Arabidopsis (Angkawijaya & Nakamura, 2017; Angkawijaya, Ngo, Nguyen, Gunawan, & Nakamura, 2019; Hanchi et al, 2018; Tannert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further in vitro studies revealed that another phosphatase, PPsPase1/PS2/PECP2 (phosphate starvation gene 2; At1g73010), exhibited the highest substrate activity for pyrophosphate, but also showed activity for PEtn and PCho (May et al, 2011). It is assumed that PPsPase1/PS2/ PECP2 also functions as PEC-phosphatase and uses PEtn/ PCho as substrates in vivo, because both phosphatases belong to the same HAD-like phosphatase family and are co-expressed under phosphate starvation (Angkawijaya et al, 2019;Hanchi et al, 2018). Recently, a gene sequence homologous to PECP1 and PPsPase1/PS2/PECP2 was described.…”
Section: Introductionmentioning
confidence: 99%